Disorder in KHCO 3 as Studied by EPR and DTA in Cu 2+ Doped and Gamma-Irradiated Single Crystals - Köksal, F.; Karabulut, B.; Demr, D.; Çbudak, H.; Köseolu, R. (Taylor & Francis Ltd, 2005)
Kalicinite (KHCO 3 ) single crystals were investigated by the electron paramagnetric resonance (EPR) technique in their Cu 2+ doped and gamma-irradiated states. It is observed that the behavior of the spectrum is the same at ambient and low temperatures down to 113 K in consistence with the monoclinic symmetry of the crystal. However, when the temperature is increased to 313 K, only one site signals were observed at all orientations of the magnetic field for the Cu 2+ doped samples as the site splitted signals overlap at this temperature. Furthermore, for the gamma-irradiated crystals, two sites were observed for the induced and radicals at ambient temperature for an arbitrary orientation of the magnetic field. However, when the temperature is increased to 348 K, the signals due to the radical overlap indicating only one site, but the signals due to the radical do not and continue to indicate the presence of the two sites. Therefore, we conclude that this one site transition at 313 K is due to the disordering of the proton vacancies, as the charge compensation of Cu 2+ is fulfilled by K + and proton holes. This indicates that the proton vacancies come to disorder at 313 K and the protons get disordered at 348 K. The differential thermal analysis results show two small endothermic peaks for the Cu 2+ doped and gamma-irradiated samples at 313 and 348 K that were attributed to the disorder of the proton vacancies and protons, in consistency with the EPR results.
Keywords: Cu 2+; Disorder; Doping; DTA; Electron Paramagnetic Resonance; Gamma Irradiation